2014
DOI: 10.5194/tc-8-705-2014
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in Arctic sea ice thickness and volume: new estimates and implications for trends

Abstract: Abstract. Sea ice volume has decreased in the last decades, evoked by changes in sea ice area and thickness. Estimates of sea ice area and thickness rely on a number of geophysical parameters which introduce large uncertainties. To quantify these uncertainties we use freeboard retrievals from ICESat and investigate different assumptions about snow depth, sea ice density and area. We find that uncertainties in ice area are of minor importance for the estimates of sea ice volume during the cold season in the Arc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 58 publications
4
113
0
Order By: Relevance
“…However in this region PIOMAS agrees better with in situ data (Schweiger et al, 2011). Zygmuntowska et al (2014) suggest that this discrepancy is due to the choice of sea ice density in ICESat, and they support this explanation by finding lower discrepancies between PIOMAS and CryoSat-2 (Laxon et al, 2013) which utilises an alternative sea ice density value. Stroeve et al (2014), in a comprehensive study of SIT across CMIP5 and observations, find that the spatial correlations in thickness between CMIP5 models and PIOMAS are generally higher than those between CMIP5 models and ICESat.…”
Section: Piomassupporting
confidence: 51%
See 1 more Smart Citation
“…However in this region PIOMAS agrees better with in situ data (Schweiger et al, 2011). Zygmuntowska et al (2014) suggest that this discrepancy is due to the choice of sea ice density in ICESat, and they support this explanation by finding lower discrepancies between PIOMAS and CryoSat-2 (Laxon et al, 2013) which utilises an alternative sea ice density value. Stroeve et al (2014), in a comprehensive study of SIT across CMIP5 and observations, find that the spatial correlations in thickness between CMIP5 models and PIOMAS are generally higher than those between CMIP5 models and ICESat.…”
Section: Piomassupporting
confidence: 51%
“…Lindsay et al (2014) force PI-OMAS with four different atmospheric reanalysis products producing differing results. Schweiger et al (2011) found biases in PIOMAS of 0.26 m in autumn and 0.1 m in spring when compared with ICESat (Zwally et al, 2002) although the spring bias is within the range of uncertainties found by Zygmuntowska et al (2014). Larger differences are found in the areas of thickest ice, north of Greenland and the Canadian Archipelago, with ICESat retrievals around 0.7 m larger than PIOMAS.…”
Section: Piomasmentioning
confidence: 57%
“…Taking into account algorithm uncertainties due to assumptions of ice density and snow conditions, the hypothesized decline in sea ice volume in the Arctic between the ICESat and CryoSat-2 operational periods may have been less dramatic (Zygmuntowska et al, 2014) than reported in Laxon et al (2013).…”
Section: Sea Ice Thickness and Volumementioning
confidence: 95%
“…Recent re-interpretation of ICESat data has enabled trends in sea ice volume of −1445 ± 531 km 3 per year in October/November and −875 ± 257 km 3 per year in February/March to be obtained (Zygmuntowska et al, 2014). Taking into account algorithm uncertainties due to assumptions of ice density and snow conditions, the hypothesized decline in sea ice volume in the Arctic between the ICESat and CryoSat-2 operational periods may have been less dramatic (Zygmuntowska et al, 2014) than reported in Laxon et al (2013).…”
Section: Sea Ice Thickness and Volumementioning
confidence: 99%
See 1 more Smart Citation